Parameter Correlation of Proximate Analysis and Ultimate Analysis of the Calorific Value of Coal - Wahyudi Zahar (Universitas Muhammadiyah Mataram, 2021)
Jambi Province is an area that has abundant coal potential, this is due to its location in the Jambi Sub-basin, part of the South Sumatra Basin. As one of the coal mining companies in Jambi Province, PT Kamalindo Sompurna conducts mining with the aim of being marketed and directly sold to predetermined consumers. If coal is tested for chemical properties in the form of proximate and ultimate analysis in a sustainable manner and correlated with its calorific value, the company can market or utilize coal directly or indirectly. Coal samples were taken by channel sampling method in the same seam, the number of samples obtained was 48 samples per 5 cm interval. The number of samples is then reduced to 5 samples with the composite method based on certain intervals. The caloric value of coal in the research area ranges from 4300 - 5300 cal / gr, the caloric value is correlated with the results of proximate and ultimate analysis using simple linear regression statistics. The results obtained between the 9 analysis parameters based on this correlation indicate that the levels of flying matter, ash, carbon content and oxygen levels have a strong correlation as indicated by the correlation value in sequence is 0.98; -0.93; 0.88; -0.89. After conducting a study based on these parameters and correlation values, researchers can provide references related to the use of coal in processing and its use as fuel, both in the power generation industry and processing of cement raw materials and so on.